2021
DOI: 10.3390/molecules26196082
|View full text |Cite
|
Sign up to set email alerts
|

Study on Nuclear Magnetic Resonance Logging T2 Spectrum Shape Correction of Sandstone Reservoirs in Oil-Based Mud Wells

Abstract: The oil-based mud filtrate will invade the formation under the overbalanced pressure during drilling operations. As a result, alterations will occur to the nuclear magnetic resonance (NMR) response characteristics of the original formation, causing the relaxation time of the NMR T2 spectrum of the free fluid part to move towards a slower relaxation time. Consequently, the subsequent interpretation and petrophysical evaluation will be heavily impacted. Therefore, the actual measured T2 spectrum needs to be corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…10. Sun et al, (2021) established a morphological correction model of NMR T 2 spectrum in oil-base mud invaded zone by comparing the difference of NMR T 2 response in oil-based mud and water-based mud wells; This is crucial for accurate interpretation and petrophysical evaluation during NMR logging. Two oil-based mud and three water-based mud wells, in the Xihu Sag sandstone gas formations in the East China Sea basin, were used as a source of the logging data.…”
Section: Evaluation Of Mud Filtrate Invasion Characteristicmentioning
confidence: 99%
“…10. Sun et al, (2021) established a morphological correction model of NMR T 2 spectrum in oil-base mud invaded zone by comparing the difference of NMR T 2 response in oil-based mud and water-based mud wells; This is crucial for accurate interpretation and petrophysical evaluation during NMR logging. Two oil-based mud and three water-based mud wells, in the Xihu Sag sandstone gas formations in the East China Sea basin, were used as a source of the logging data.…”
Section: Evaluation Of Mud Filtrate Invasion Characteristicmentioning
confidence: 99%
“…Therefore, with the gradual advancement of exploration and the development of low-porosity and low-permeability sandstone reservoirs, the study of the microscopic mechanism of formation damage by drilling fluid has received increasing attention in recent years. At present, the experimental methods for studying the damage to rocks caused by drilling fluid at the microscopic scale include thin-section observations [13,14], scanning electron microscope (SEM) observations [15,16], X-ray diffraction (XRD) [17], nuclear magnetic resonance (NMR) imaging [18], CT scanning [19], etc. The main idea of these methods is similar: first, obtaining rock samples (from drilling) before drilling fluid damage and rock samples (from core flooding experiments) after drilling fluid damage and then scanning or observing the rock samples before and after drilling fluid damage at the microscopic scale, and comparing the differences between them to determine the characteristics of formation damage.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of the XRD method is that the influence of the composition and content of the solid particles in drilling fluid on the formation damage can be quantitatively analyzed [17]. The advantage of the NMR imaging and CT scanning methods is that the damage of core samples by drilling fluid can be observed from a three-dimensional scale, but the resolution of the images is relatively low, such that the characterization of the microscopic details is insufficient [18][19][20]. In addition, some studies have shown that drilling fluids with different liquid components (oil and water) undergo changes in viscosity, dynamic shearing force, static shearing force, wettability, and other properties under formation temperature and pressure conditions, which At present, the experimental methods for studying the damage to rocks caused by drilling fluid at the microscopic scale include thin-section observations [13,14], scanning electron microscope (SEM) observations [15,16], X-ray diffraction (XRD) [17], nuclear magnetic resonance (NMR) imaging [18], CT scanning [19], etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oil Industry : In their work entitled “ Study on Nuclear Magnetic Resonance Logging T 2 Spectrum Shape Correction of Sandstone Reservoirs in Oil-Based Mud Wells ” Sun et al presented a need to improve the NMR logging data in order to accurately determine the physical parameters of the surrounding sandstone reservoirs to improve drilling operations [ 1 ]. During drilling operations, overbalanced pressure causes the infiltration of oil-based drilling lubricant into the surrounding sediment, resulting in a shorter T 2 relaxation.…”
mentioning
confidence: 99%